Nocturnal Knee Pain Increases With the Severity of Knee Osteoarthritis, Disturbing Patient Sleep Quality. Issue 7 (July 2014) - Sasaki, Eiji; Tsuda, Eiichi; Yamamoto, Yuji; Maeda, Shugo; Inoue, Ryo; Chiba, Daisuke; Okubo, Noriyuki; Takahashi, Ippei; Nakaji, Shigeyuki; Ishibashi, Yasuyuki
<x xml:space="preserve">Abstract</x> Objective Sleep disturbances frequently accompany chronic pain from osteoarthritis (OA). Effective management of sleep disturbances may require successful treatment of chronic pain, a key factor in the clinical evaluation of knee OA. However, the relationship between the severity of knee OA and sleep quality is unclear. Our purpose was to correlate the prevalence of nocturnal knee pain with different OA severity levels and to determine its influence on sleep quality. Methods Subjects included 1, 214 local volunteers with mean ± SD age 58.1 ± 13.0 years. The existence and severity of knee OA were determined by the Kellgren/Lawrence (K/L) grade, and joint space widths were measured. The presence of nocturnal knee pain and Knee Injury and Osteoarthritis Outcome Scores (KOOS) were assessed by self‐completed questionnaires. Sleep quality was evaluated by the Pittsburgh Sleep Quality Index. Knee‐related factors affecting sleep quality were detected using statistical methods. Results The prevalence of nocturnal knee pain was 3.6%, 6.9%, 19.4%, 32.7%, and 75.0% in K/L grades 0, 1, 2, 3, and 4, respectively. Also, prevalence significantly increased with OA severity (P < 0.001). Sleep problems also increased with K/L grade (P = 0.038), and KOOS quality of life (QOL) was significantly lower in those with OA and sleep problems. Logistic regression showed that sleep problems were related to joint space narrowing (P = 0.016) and nocturnal knee pain (P = 0.039). Severe OA also disturbed onset and maintenance of sleep. Conclusion The prevalence of nocturnal knee pain and sleep problems increased with the severity of OA, impacting QOL. These results suggest the necessity of appropriate nocturnal pain control.